A 5‐channel local B0 shimming coil combined with a 3‐channel RF receiver coil for rat brain imaging at 3 T. Issue 1 (15th September 2022) - Chen, Qiaoyan; Luo, Chao; Tie, Changjun; Cheng, Chuanli; Zou, Chao; Zhang, Xiaoliang; Liu, Xin; Zheng, Hairong; Li, Ye
Abstract : Purpose: We aimed to improve B0 magnetic field homogeneity and minimize the interference between RF coils and local B0 shimming coils with few channel numbers. Methods: To design and construct the prototype for B0 shimming of the rat brain, we first evaluated the interferences of single shimming loops on RF receiver loops. Then, B0 shimming of the whole rat brain was implemented using an optimization procedure. The positions and currents of the local shimming coils with channel numbers from 3 to 6 were optimized to improve shimming performance. Based on the simulation results, a 5‐channel local shimming coil, combined with a 3‐channel RF receiver coil, was constructed and evaluated by animal experiments. Results: There was marginal SNR loss within 5% after integrating the local shimming coil into the RF receiver coil. With respect to the Siemens standard shims up to second order, the B0 inhomogeneity in one whole rat brain was reduced from 39.6 Hz to 24.7 Hz by using the local shimming coil. A large portion of the EPI distortions was recovered after using the 5‐channel local shimming coil. The temporal SNR using the local shimming coil was higher than that using the Siemens standard shims up to second order, with an improvement of more than 24%. Conclusions: The local shimming coil can improve B0 magnetic field homogeneity despite minor effects on the RF coil and can benefit a variety of applications that are sensitive to B0 inhomogeneity. Nevertheless, EPI for rat brain is still very challenging. Abstract : Click here for author‐reader discussions